Characteristics and Management of Anterior Segment Dysgenesis in Pediatric Ophthalmology - Irawati Irfani; Sarah Nurul Ramadanti; Astrid Feinisia Khairani (Majalah Oftalmologi Indonesia, 2016)
Background: Anterior segment dysgenesis (ASD) is congenital anomaly caused by malformation of the eyeball during early pregnancy. Intrauterine ASD leads to disorder in maturation of anterior segment of the eye and its complications could interfere the normal visual development. There are several types of ASD and variability of its management. In this report, we described characteristic of ASD including its management in Cicendo Eye Hospital, Bandung. Methods: This is a retrospective descriptive study from medical records of patients with ASD in Cicendo Eye Hospital, Bandung since January 2012 until December 2014. Data were collected based on total sampling with inclusion criteria. All data were analyzed by statistical software. Results: There were 99 patients with range of age 1-day-old until 18-years-old who met the inclusion criteria of this study. Patient of ASD was commonly brought to the hospital at infant age (55.5%), boys in 51.5% patients and mostly came from out of town (70.7%). Thirty-seven percent of their mothers had history of drug consumptions during pregnancy and 30% born prematurity. Seventy percent cases of ASD were bilateral, 80.8% without systemic disease, and congenital glaucoma was the most common type of ASD (30.7%). The most common management was observation in 45.5% cases, followed by combination of surgical and medicamentosa in 30.3% cases. Conclusion: ASD is a congenital condition which has variability in types and management. Early recognition of this condition is necessary to decide the appropriate treatment to assist visual development and rehabilitation. Â Keywords: anterior segment dysgenesis, characteristics, management Â Â